Aspectos da germinação e da conservação de sementes de espécies do gênero Tabebuia (Bignoniaceae) - Borba Filho, Aluisio Brigido (Universidade Federal de São Carlos, 2006)
The genus Tabebuia in the family Bignoniaceae comprises about 100 species, several of which have medicinal, ornamental, and timber value, in addition to their environmental importance. These species produce large amounts of seeds, with a short viability period under natural conditions. In the present research, studies were developed on germination and conservation aspects of seeds in species of the genus Tabebuia. Initially, substrates were evaluated to be used in seed germination tests for the species T. aurea (Manso) Benth. & Hook., T. impetiginosa (Mart.) Standl., T. ochracea (Cham.) Standl., T. roseo-alba (Ridl.) Sand., and T. serratifolia (Vahl.) Nich. The following substrates were tested: on sand, on vermiculite, on sand+vermiculite, on paper (two sheets of blotting paper) and between sheets (two sheets of blotting paper under and one sheet over the seeds). For T. impetiginosa seeds, these substrates are suitable for use in germination tests. For the other species, the most suitable substrates were: on sand, on paper, and between sheets for T. aurea; between sheets for T. ochracea and T. roseo-alba; and on sand and between sheets for T. serratifolia. In another study we attempted to identify a suitable condition to store T. roseo-alba and T. impetiginosa seeds, as well as to evaluate methods to estimate alterations in the viability and vigor of those seeds. Different groups of seeds were placed in clear plastic bags, Kraft paper bags, and cans. The seeds were then stored for up to 300 days under laboratory, refrigerator, and refrigerated chamber conditions. Seed water content, germination percentage and velocity, and electric conductivity were determined at the onset of storage and thereafter at every 60 days. The best T. roseo-alba and T. impetiginosa seed conservation condition was obtained with cans maintained in the refrigerator. T. impetiginosa seeds can also be kept in plastic bags, paper bags, or cans when stored in refrigerated chamber. Seed vigor alterations in these species are initially identified based on germination velocity. In the third study, we evaluated accelerated aging effectiveness in detecting vigor variations in T. roseo-alba and T. impetiginosa seeds. Seeds of these species were submitted to accelerated aging under temperatures of 40 or 45ºC, for periods of 24, 48, 72, 96, 120, and 144 hours. After those periods, germination and plantlet emergence tests were conducted, and field emergence index values were calculated. We verified that accelerated aging is effective to detect seed vigor variations in T. roseo-alba and T. impetiginosa. When aging is conducted at 45°C, differences in viability and vigor occur first. Traits such as germination percentage and velocity, plantlet emergence, and incorporated biomass can be recommended as seed vigor indicators, using accelerated aging. Under more drastic accelerated-aging conditions, no correspondence is observed between data obtained in the field and in the laboratory.
Keywords: Germinação; Tabebuia; Plantas florestais - sementes; Vigor de sementes; CIENCIAS BIOLOGICAS::ECOLOGIA